High-frequency broadband (HFB) peak latency timing changes with memory. - Adam J. O. Dede (11554007) (2025)
A. In grey, four sequentially recorded examples of single-trial HFB traces are displayed from a single channel. In black, the same traces are displayed after application of a Gaussian smoothing kernel. The broken vertical red line indicates the behavioral RT of each trial. The dashed vertical black line indicates image onset. The green dots indicate the peak HFB activity on each trial. Note the lack of consistency in peak latency. This panel can be regenerated using data contained in HFB_singleTrialmtl_sub_image.mat and code in Figure1C_2A.m [112]. B. The heatmap displays single-trial HFB time series from channels in the hippocampus during subsequent hit trials. Trials have been sorted by latency of the peak HFB power. White dots indicate the behavioral RT of each trial, which was a poor predictor of the latency of the HFB power peak. This panel can be regenerated using data contained in HFB_singleTrialmtl_sub_image.mat and code in Figure2B.m [112]. C. Each cumulative distribution plot displays the timing of the latency of peak HFB activity across all trials for subsequent hits (top left), subsequent misses (top right), retrieval hits (bottom left), and retrieval misses (bottom right). Each region’s trial distribution is shown with a different line. Because different numbers of trials were observed in different behavioral conditions and for different regions, trial is plotted as a percentile of trials on the y-axis. Because reaction times were variable between individuals and conditions, time is plotted on the x-axis as a proportion of time such that 0 is image onset and 1.0 is behavioral response. This panel can be regenerated using data contained in the HFB_singleTrial folder and code in Figure2C.m [112]. D. Each grouped scatter plot displays the mean time of peak HFB latency for each channel grouped by region. Time relative to image onset is displayed as a proportion on the y-axis. Error bars display the 83% confidence interval around model estimates [113,114]. For example, note that while the hippocampus (light blue) and parahippocampal gyrus (red) led the dlPFC and pPFC during successful encoding, these PFC regions were active simultaneously with the Hip during successful retrieval. This panel can be regenerated using data contained in trialLatDat_RTfix.csv and code in Latency_LME_modeling.Rmd [112].